Role of Cadmium and Lead in Nephrotoxicity - Fatima, Hafiza Samar (Edelweiss Applied Science and Technology, 2018)
Nephrotoxicity stands amongst the most widely recognized kidney issues and happens when human body is presented to a medication or toxins that give harm to kidneys. At the point when kidney harm happens, patient cannot free his assortment of abundance urine, and squanders. It can be acute and chronic. Lead and cadmium are the two most commonly known nephrotoxic metals. People who work or live in such environmental settings which made them exposed to these toxins are at risk. Prolonged exposure to these metals leads to their accumulation in tissues especially kidneys. Proximal tubular dysfunction, hypertension, hyperuricemia and decreased glomerular filtration rate are the common effects of cadmium and lead nephrotoxicity respectively. Proper medication can reduce these dysfunctional ties but best treatment is to reduce exposure so one can avoid the accumulation of these toxins in kidneys and other tissues.